Орчин цагийн монгол хэлний грек, латин гаралтай үг хэллэгийн шинж байдал, тоо хэмжээ, түүнээс сургамж авах нь: Status and usage of Greek and Latin words and expressions in modem Mongolian, lesson from it - Б., Элбэгзаяа (Mongolian Studies, 2023)
1. Usage of Greek and Latin originated words and terminologies had become more popular in Mongolia since 1990 because international relationship of our country had become more open and unrestricted and social, political and economic environment has been reshaping. According to the statistics, foreign words which are being used in modem Mongolian since 1990 are considerably higher than those used in 1921-1990 and before. However it would not be appropriate to criticize that there is over usage of foreign words in lexis of Mongolian. 2. Although foreign words such as Greek and Latin originated words are used popularly in modem Mongolian particularly in media, advertisement and everyday speech due to advanced need of foreign language as a requirement of modem society, those should not be used all the time. In one word we are ignoring rich resource of our own language. 3. Furthermore proper actions should be taken promptly on proper usage of native language and its respective by running accurate research on western and eastern (loan) words in Mongolian lexis and its origin and percentage and reflecting its result on curriculum of all level of schools, “Law of Official Language”, “Law of Press Freedom”, “Law of Mongolian National Public Television and Radio” and “Law of Advertisement” precisely. Changing foreign words into Mongolian form and using them suitably and effectively are our priority as for native language experts.